Long-term dental intervention and laboratory examination in a patient with Vitamin D-dependent rickets type I: A case report. Issue 41 (9th October 2020) - Liu, An-Qi; Zhang, Li-Shu; Guo, Hao; Wu, Mei-Ling; Li, Tian-Yi; Xuan, Kun; Wei, Ke-Wen
Abstract: Rationale: Vitamin D-dependent rickets type I (VDDR-I) is a rare form of rickets, which is an autosomal recessive disease caused by 1α-hydroxylase enzyme deficiency. However, long-term dental management and microscopic morphology of teeth remain largely unclear. Patient concerns: We report the case of a 10-year-old Chinese boy complaining of yellowish-brown teeth with extensive caries. Diagnoses: Clinical and laboratory examinations were performed, and VDDR-I was confirmed. Scanning electron microscopy confirmed amelogenesis imperfecta. Interventions: The patient had been taking drugs intervention for VDDR-I from the age of 3 years. The decayed teeth were treated, and metal-preformed crowns were placed to prevent further impairment. Sequence tooth extraction and remineralization therapy were also performed. Outcomes: After 3 years of follow-up, the patient exhibited normal tooth replacement and an acceptable oral hygiene status. However, the new erupted teeth had amelogenesis imperfecta. Lessons: This case is the first to confirm amelogenesis imperfecta in a patient with VDDR-I that was not prevented by drug intervention. Importantly, it provides evidence that long-term dental intervention in patients with VDDR-I can result in an acceptable oral hygiene status. Therefore, early and long-term dental intervention is necessary in VDDR-I patients.